Exploring Future Hybrid Accounting: A Review of Water Accounting and Management Research - Siyun Liao; Aila Khan (Australasian Accounting, Business and Finance Journal, 2022)
A review of the literature provides empirical evidence that companies use water accounting (WA) to address water shortages and water management issues. Our systematic review suggests two key points: first, phenomena such as water shortages and freshwater scarcity are no longer limited to less developed areas in Asia. Developed economies may also experience a water crisis. Second, in view of the increased pressure from stakeholders, there is a growing tendency amongst firms to manage risks around water as a resource and to implement rigid control of water consumption.
Keywords: water accounting; literature review; isomorphism; hybrid accounting; Sustainable development goals